Analisis Yuridis Hak-Hak Asasi Tersangka Pidana Dalam Proses Penyidikan - Slamet Santoso; Tofik Yanuar Chandra; Santrawan Paparang (JOURNAL of LEGAL RESEARCH, 2022)
In Indonesia, the criminal justice system consists of numerous steps, including investigation, investigation, prosecution, and trial. The investigative stage consists of a series of measures taken by investigators in accordance with and according to the manner outlined in this statute in order to discover the suspect and collect evidence that clarifies the nature of the criminal act. In addition, the suspect is a person who, based on preliminary information, should be accused of committing a crime because of his behavior or circumstances. The idea of presumption of innocence stipulates that all parties engaged in a criminal case must be presumed innocent until a court determines guilt. This principle must be observed by law enforcement throughout the investigation, prosecution, and court examination processes. This right is guaranteed by Article 8, paragraph 1, of Law No. 48 of 2009 on Judicial Power, which states that any individual who is suspected, arrested, detained, prosecuted, or brought before a court must be presumed innocent until a court decision declares his guilt and acquires permanent legal force. Suspects have rights and are protected by the law, despite the fact that they are suspected of committing a crime. This research is normative legal in nature. This study provides input and opinions that law enforcers, in this case Police Investigators, must implement the Presumption of Innocence Principle and defend human rights, since everyone must be deemed innocent prior to a court ruling declaring his guilt and acquiring permanent legal force. In order to expedite the investigative examination process, suspects should submit truthful and uncomplicated information, so that there are no factors that can lead to violence against suspects or abuses of their human rights.